Peran ChatGPT dalam Meningkatkan dan Menghambat Proses Belajar Mahasiswa di Era Digital - Dya Arzepta Maiza; Nayla Sifa Syabila; Salwa Aprila; Harun Mukhtar; Rahmad Gunawan; Januar Al Amien (Coding: Journal of Computing and Software Engineering, 2025)
The rapid development of generative AI, such as ChatGPT, has had a significant impact on higher education, particularly in open and distance learning (ODL) systems. This transformation is not only changing the way students access information but also influencing the interaction patterns between lecturers and students in digital environments. Research shows that while ChatGPT offers advantages such as fast information access, writing assistance, instant feedback, and personalized learning tailored to individual needs, its unwise use can reduce intrinsic learning motivation, trigger over-dependence, and hinder the development of students' critical thinking, analytical skills, and creativity. Furthermore, various ethical challenges arise, such as the potential for plagiarism, data privacy violations, algorithmic bias, and low AI literacy among users. Therefore, an adaptive AI utilization strategy is needed, integrated into the curriculum, and based on clear ethical principles and regulations to support innovative learning without compromising students' academic integrity and intellectual abilities in a sustainable manner.